2020
DOI: 10.1152/ajpendo.00276.2019
|View full text |Cite
|
Sign up to set email alerts
|

miR-130b is a potent stimulator of hepatic very-low-density lipoprotein assembly and secretion via marked induction of microsomal triglyceride transfer protein

Abstract: miR-130b is a microRNA whose expression is particularly elevated within adipose tissue and in the circulation in diabetic states. Hepatic miR-130b expression has been linked to hepatocellular carcinoma and changes in lipid metabolism. Here, we investigated the role of miR-130b in hepatic lipid homeostasis and lipoprotein export. We observed that overexpression of miR-130b-3p or -5p in HepG2 cells markedly enhanced the secretion of very-low-density lipoprotein (VLDL) particles, enhanced the secretion of [3H]gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Interestingly, we also show that higher exosomal miR-130b levels are associated with better lipid profiles. miR-130b is a regulator of lipid homeostasis, targeting lipid oxidation and LDL receptor expression [ 87 , 88 ]. It is plausible that the higher miR-130b found in CLL-FIT patient exosomes is limiting the CLL-like cell growth utilization of lipids and promoting our observed lower growth.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we also show that higher exosomal miR-130b levels are associated with better lipid profiles. miR-130b is a regulator of lipid homeostasis, targeting lipid oxidation and LDL receptor expression [ 87 , 88 ]. It is plausible that the higher miR-130b found in CLL-FIT patient exosomes is limiting the CLL-like cell growth utilization of lipids and promoting our observed lower growth.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we show here that higher exosomal miR-130b expression is associated with better lipid profiles suggesting that miR-130b has a role in CLL lipid homeostasis. Indeed, miR-130b is a potential regulator of lipid homeostasis, targeting lipid oxidation and LDL receptor expression [89, 90]. That said, dyslipidemia and hypercholesterolemia also likely have complex roles in the pathogenesis of CLL, but these are not fully understood [91, 92].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that bta-miR-130a/b suppressed cellular TAG and lipid droplet accumulation, by directly targeting PPARG and CYP2U1 in bovine preadipocytes [ 17 ]. miR-130b promoted hepatic VLDL assembly and secretion by increasing MTP expression and TAG mobilization in immortalized human hepatocytes [ 18 ]. In GMEC, miR-130b impaired adipogenesis and targeted both the coding sequence and 3′-untranslated regions (UTR) of PGC1α [ 19 ].…”
Section: Introductionmentioning
confidence: 99%